The Role Of The Startup of “Big Edu Indonesia” in improving Research Esearch Ability Of Students In High School - Nurkholifatul Maula (Balitbangda Provinsi Jambi, 2022)
Research competitions for high school students are increasingly being held. Several prestigious research competitions at the national level include: LKIR BRIN, OPSI and MYRES. Along with the increasingly prestigious competition, the government began to make a policy that favorite schools need to participate in research competitions. So that each school competes with each other to include students in research competitions. Educational startups such as Big Edu Indonesia become third parties for schools. This study aims to describe the Big Edu Indonesia mentoring service and the impact of the service on students' research abilities. The method used is qualitative. As for the results of this research, the mentoring service for scientific competitions is carried out with the main curriculum, namely preparing the background, theoretical basis and research methods. The learning method used is learning by doing, with the help of media zoom meetings, google meet, discord and whatsapp. The impact of these services can improve students' innovative thinking skills to develop research ideas, make it easier for students to find references, and develop scientific methods.Keywords: Big Edu Indonesia, research abaility